An unquiet mind - Jamison, Kay R (New York : Vintage Books, 1996)
"Dr. Jamison is one of the foremost authorities on manic-depressive (bipolar) illness; she has also experienced it firsthand. For even while she was pursuing her career in academic medicine, Jamison found herself succumbing to the same exhilarating highs and catastrophic depressions that afflicted many of her patients, as her disorder launched her into ruinous spending sprees, episodes of violence, and an attempted suicide. Here Jamison examines bipolar illness from the dual perspectives of the healer and the healed, revealing both its terrors and the cruel allure that at times prompted her to resist taking medication."--Provided by publisher
The wild blue yonder -- A not so fine madness -- This medicine, love -- An unquiet mind
Keywords: Jamison, Kay R. -- Mental health; Manic-depressive persons -- United States -- Biography; Women college teachers -- United States -- Biography; Bipolar Disorder; Biography; Biography